Static and dynamic impacts of three to six-phase conversion of selected transmission line in an electric energy system - Mustaffa, Wazir (Universiti Teknologi Malaysia, 2006)
Electricity is considered as the driving force for a country, which is undergoing rapid industrialization. Constrains on the availability of land and planning permission for overhead transmission lines have renewed interest in techniques to increase the power carrying capacity of existing right-of-ways (ROW). Six-phase transmission appears to be the most promising solution to the need to increase the capability of existing transmission lines and at the same time, respond to the concerns related to electromagnetic fields. One of the main advantages of sixphase transmission is that a six-phase line can carry up to 73% more electric power than a three-phase double-circuit line on the same transmission right-of-way. However, this conversion will have impacts on the power system operations. In this project, the digital load flow, short circuit, and transient stability cases of the IEEE Test Systems and 19-Bus TNB Kelantan System is investigated in time domain considering conversion of three-phase double-circuit to six-phase single-circuit transmission system by using Power System Computer Aided Design/Electromagnetic Transient and Direct Current PSCAD/EMTDC program. These studies were performed in sufficient detail to determine how the six-phase conversion will affect steady state operation, fault current duties, and system stability. A laboratory prototype of Kuala Krai to Gua Musang TNB Kelantan Thevenin equivalent systems is developed to validate the simulation results. From the simulation results, it has been shown that the IEEE Test Systems and 19-Bus TNB Kelantan System with six-phase single-circuit transmission has a better stability limits compare to the three-phase double-circuit transmission. Besides, load flow results shown the voltage level at all buses are remains in the acceptable limits. Furthermore, fault current for the same type of fault on the mid point of selected transmission line is reduced while six-phase transmission is used compare to threephase double-circuit.